Occupational Safety and Worker Preferences: Is There a Marginal Worker? - Kahn, Shulamit (The Review of Economics and Statistics, 1987)
Occupational safety levels in nonunion firms are empirically shown to reflect only the preferences of workers with zero to three years job tenure. Therefore, ex post, the market is inefficient even if workers were optimizing at the time of hire since there are trades possible among workers that would make all workers better off. The workers who are ignored in the safety-setting process, those workers with more than three years job tenure, prefer less, not more, safety. Copyright 1987 by MIT Press.